The association of serum vitamin D–binding protein and 25‐hydroxyvitamin D in pre‐operative and post‐operative colorectal cancer. Issue 5 (13th December 2019) - Liang, Yuanzi; Jiang, Liejun; Chi, Xiaowei; Hochwald, Steven; Qiu, Feng; Luo, Yanfang; Lu, Qiuwei; Yang, Xiafang; Huang, Huayi; Xu, Junfa
Abstract: Background: The association between vitamin D–binding protein (VDBP) and 25‐hydroxyvitamin D (25 (OH)D) with colorectal cancer (CRC) is still ambiguous. This study was to further investigate the relationship between serum VDBP, 25 (OH)D levels and the clinical and pathological features of patients with CRC. Methods: Enzyme‐linked immunosorbent assay (ELISA) and chemiluminescence immunoassay were used to analyze the VDBP and 25(OH)D concentrations in serum. Pearson's correlation analysis was applied to evaluate the association between serum VDBP and 25(OH)D levels in CRC. Conditional logistic regression was performed to analyze the prediction value of serum VDBP or 25(OH)D as a risk factor for CRC. Results: The serological levels of 25(OH)D in patients were significantly lower than in healthy individuals, while VDBP levels were significantly higher than in healthy controls. The serum VDBP in pre‐operative was significantly lower than in post‐operative samples, while the serum 25(OH)D from pre‐operative patients was significantly higher than post‐operative patients. Patients with tumors with higher stage and increased lymph node involvement had lower serum post‐operative VDBP levels. In addition, our results showed that the pre‐operative VDBP level is a risk factor of CRC. Conclusions: The levels of serum 25(OH)D and VDBP were both associated with CRC. Thus, serum 25(OH)D and VDBP levels might be of value in evaluating the pathogenesis and risk of CRC in the future. Moreover, serum VDBP or 25(OH)D levels were associated with patient's clinical and pathological features providing data for risk and prognostic prediction.